INFLUENCE OF THE DIGITAL ECONOMY ON THE COUNTRY’S DEVELOPMENT (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article explores the possibilities of the digital economy, as well as the gradual transition to the digital economy of Uzbekistan in the context of globalization and technological development of the world economy. The influence of the digital economy in the development of the country’s economy, social sphere and public administration.